2019
DOI: 10.1038/s41598-019-47261-x
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin-induced oxidative stress leads to inhibition of Na+/K+-ATPase (NKA) in canine cancer cells

Abstract: The Na + /K + -ATPase (NKA) complex is the master regulator of membrane potential and a target for anti-cancer therapies. Here, we investigate the effect of drug-induced oxidative stress on NKA activity. The natural product, plumbagin increases oxygen radicals through inhibition of oxidative phosphorylation. As a result, plumbagin treatment results in decreased production of ATP and a rapid increase in intracellular oxygen radicals. We show that plumbagin induces a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This conclusion was found by Qi et al (2017) who proved PLB induced apoptosis of canine cancer cells via oxidative stress by inhibition of oxidative phosphorylation. Thus, it was concluded that PLB-induced oxidative stress led to the inhibition of NKA in canine cancer cells [ 88 ].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…This conclusion was found by Qi et al (2017) who proved PLB induced apoptosis of canine cancer cells via oxidative stress by inhibition of oxidative phosphorylation. Thus, it was concluded that PLB-induced oxidative stress led to the inhibition of NKA in canine cancer cells [ 88 ].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…12). www.nature.com/scientificreports/ Thus, an inhibition of sodium efflux ATPase would cause an increase in intracellular sodium concentration, which will trigger ROS, DNA damage and, hence, apoptosis [44][45][46] . At the level of cell organelles such as mitochondria, a plausible inhibition of FoF1 ATPase would cause a considerable decrease of ATP and strong changes in depolarization of the mitochondrial membrane 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In Chapter 4, it has been shown that ROS regulates the activity of SrcK in an NKA signalosome; however, ROS also regulates the NKA pumping activity. Alharbi et al [ 165 ] showed that ROS induced a decrease in the NKA activity, which led to apoptosis of canine cancer cells, and this effect was abrogated by pretreatment with an antioxidant N-acetylcysteine. The mechanism for this regulation of NKA activity lies in the S-glutathionylation of l -Cys residues, which leads to conformational change preventing ATP binding and thus reducing NKA activity [ 166 , 167 ].…”
Section: Regulation Of Na + /K + -Atpase Activitymentioning
confidence: 99%